Contract Tree Farming in Tamil Nadu - a Successful Industrial Farm Forestry Model - Parthiban, K. T.; Seenivasan, R.; Govinda Rao, M. (Indian Forester, 2010)
The State of Tamil Nadu is housed with 39 paper mills of which two mills viz., Tamil Nadu Newsprint and Papers Ltd, Karur and Seshasayee Paper Board, Erode are the wood based paper industries. These two industries utilize around 4 lakh tonnes of woody biomass, which are mostly derived from Casuarina and Eucalyptus plantations of Tamil Nadu Forest Plantation Corporation and partly from farm lands. But recently, both the mills have expanded their paper production, which requires nearly 8-10 lakhs tonnes of wood pulp against the current availability of nearly 3.5 -4.0 lakh tonnes. This ushered in a large gap between the demand and supply, thus necessitates alternate sources for raw material. To meet the growing demands and also to promote pulp wood plantations as per the guidelines of 1988 forest policy, both the industries have initiated farm and agroforestry plantations through contract farming system by adopting tri and quad-partite models. In this system, Casuarina and Eucalyptus have been promoted as pulp wood plantations. The contract farming facilitates supply of quality planting materials to the farmers at subsidized prices coupled with assurance of minimum support price and credit facilities through financial institutions. This paper discusses the success of contract farming along with the area covered under various districts of the state.